Oxygen out, sulfur in: The alkali metal sulfidotungstates K2[WS4] and novel Na2[WS4] ⋅ 4 H2O - Knies, Benjamin; Hartenbach, Ingo (Zeitschrift für anorganische und allgemeine Chemie (1950), 2022)
An attempt to synthesize a holmium sulfidotungstate using potassium polysulfides as reactive flux resulted in orange single crystals of K2[WS4], isotypic to K2[MoS4] (orthorhombic; Pnma; a=935.10(3), b=694.22(2), c=1221.85(4) pm; Z=4). A similar attempt to obtain a neodymium sulfidotungstate with sodium polysulfide yielded a violet substance, which underwent hydrolysis yielding orange‐yellow single crystals of Na2[WS4] ⋅ 4 H2O (monoclinic, C2/c, a=1098.08(4), b=904.46(3), c=1144.27(4) pm, β=101.577(3)°, Z=4). Further attempts to synthesize these products deliberately as single phase materials only proved to be successful for K2[WS4] but not for Na2[WS4] ⋅ 4 H2O. Both compounds contain non‐condensed [WS4]2− tetrahedra, which surround the alkali metal cations with coordination numbers of nine and eight in K2[WS4]. In Na2[WS4] ⋅ 4 H2O, the sodium cations are coordinated by two sulfide anions plus four water molecules, resulting in a coordination number of six. Besides crystal structure determination, infrared and single crystal Raman spectra were collected and the optical band gap of K2[WS4] was determined.